2011
DOI: 10.1039/c0ob01001d
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the whole range of CuAAC mechanisms by DFT calculations—on the intermediacy of copper acetylides

Abstract: The archetypal Cu(I)-catalyzed alkyne-azide click cycloaddition (CuAAC) has been explored thoroughly via density functional calculations, modeling copper nuclei with the LANL2DZ basis set and aqueous environments with CPCM solvation. All the mechanistic proposals, ranging from the intermediacy of copper acetylides to π-complexes and multinuclear clusters have been compared. The known features of the CuAAC reaction such as the observed second order kinetics for the Cu(I) species and the marked regioselectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 40 publications
2
59
0
1
Order By: Relevance
“…This mechanistic picture was supported by recent calculations carried out by the group of Cantillo [199]. In their DFT study, the authors compare different mechanistic proposals from literature on the same level of theory (B3LYP/LANL2DZ, solvent model CPCM for water).…”
Section: Reviewmentioning
confidence: 59%
“…This mechanistic picture was supported by recent calculations carried out by the group of Cantillo [199]. In their DFT study, the authors compare different mechanistic proposals from literature on the same level of theory (B3LYP/LANL2DZ, solvent model CPCM for water).…”
Section: Reviewmentioning
confidence: 59%
“…Indeed, complexes with acetylide ligands that bind copper species may be resting states of the catalyst in such click reaction mixtures that are not acidic [58c]. Following these pioneering computational works, several theoretical mechanistic investigations on the CuAAC reactions have been carried out, considering various copper systems, most of them multinuclear, and leading basically to similar qualitative conclusions [34,[58][59][60][61][62]. A recent investigation pointed out the possibility for a concerted vs. stepwise nature of the mechanism, however, depending on the ligand nature [63].…”
Section: Introductionmentioning
confidence: 99%
“…Since the early reports, a variety of transition-metal catalysts have been used for the reactions between mono-or disubstituted alkynes and azides (vide infra). For the Cu(I) catalyzed reaction, a variety of mechanisms involving Cu(I)-aryl intermediates have been proposed in which the key-step species contains either mononuclear [35] or binuclear copper species [30][31][32][33][34][35][36][37][38]. Theoretical studies of the RuAAC reaction have also been reported [28,[39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…[33] In their DFT study, the authors compare different mechanistic proposals from literature on the same level of theory (B3LYP/LANL2DZ, solvent model CPCM for water). In conclusion, they confirm dinuclear copper acetylides to be the essential catalytic intermediates, whereas the corresponding copper alkyne pcomplexes need to be deprotonated before the crucial C-N bond forming step can take place.…”
Section: Mechanistic Investigation Of the Cuaacmentioning
confidence: 99%